Age-Related Differences in Corticospinal Excitability during Observation and Motor Imagery of Balance Tasks - Mouthon, Audrey A.; Ruffieux, Jan; Keller, Martin; Taube, Wolfgang (Frontiers in Aging Neuroscience, 2016)
Postural control declines across adult lifespan. Non-physical balance training has been suggested as an alternative to improve postural control in frail/immobilized elderly people. Previous studies showed that this kind of training can improve balance control in young and older adults. However, it is unclear whether the brain of young and older adults is activated differently during mental simulations of balance tasks. For this purpose, soleus and tibialis motor evoked potentials (MEPs) and soleus H-reflexes were elicited while 15 elderly (mean±SD = 71±4.6 years) and 15 young participants (mean±SD = 27±4.6 years) mentally simulated static and dynamic balance tasks using motor imagery, action observation (AO), or the combination of AO and MI (AO+MI) . Young subjects displayed significant modulations of MEPs that depended on the kind of mental simulation and the postural task. Elderly adults also revealed differences between tasks, but not between mental simulation conditions. Furthermore, the elderly displayed larger MEP facilitation during mental simulation (AGE-GROUP; F1,28=5.9; p=0.02) in the soleus muscle compared to the young and a task-dependent modulation of the tibialis background EMG activity. H-reflex amplitudes and background EMG (bEMG) in the soleus showed neither task- nor age-dependent modulation. As neither mental simulation nor balance tasks modulated H-reflexes and bEMG in the soleus muscle, despite large variations in the MEP-amplitudes, there seems to be an age-related change in the internal cortical representation of balance tasks. Moreover, the modulation of the tibialis bEMG in the elderly suggests that aging partially affects the ability to inhibit motor output.